How Children’s Cognitive Reflection Shapes Their Science Understanding - Young, Andrew G.; Shtulman, Andrew (Frontiers in Psychology, 2020)
Learning science requires contending with intuitions that are incompatible with scientific principles, such as the intuition that animals are alive but plants are not or the intuition that solids are composed of matter but gases are not. Here, we explore the tension between science and intuition in elementary-school-aged children and whether that tension is moderated by children’s tendency to reflect on their intuitions. Our participants were children between the ages of five and twelve (n = 142). They were administered a statement-verification task, in which they judged statements about life and matter as true or false, as well as a cognitive reflection test, in which they answered “brain teasers” designed to elicit an intuitive, yet inaccurate, response that could be corrected upon further reflection. Participants also received a tutorial on the scientific properties of life or matter, sandwiched between two blocks of the statement-verification task. We found that participants’ performance on the statement-verification task, which pitted scientific conceptions against intuitive conceptions (e.g., “cactuses are alive”), was predicted by their performance on the cognitive reflection test, independent of age. Children who demonstrated higher levels of cognitive reflection verified scientific statements more accurately before the tutorial, and they demonstrated greater gains in accuracy following the tutorial. These results indicate that children experience conflict between scientific and intuitive conceptions of a domain in the earliest stages of acquiring scientific knowledge but can learn to resolve that conflict in favor of scientific conceptions, particularly if they are predisposed toward cognitive reflection.